Compete or Cooperate: Understanding of the Relationship Levels of Firms within same Industry - Shaker, Fahim (Asian Business Review, 2015)
This paper tries to address various dimensions of the firm relationship that are competing in the same industry. Competitive strategies play important role for a firm's survival and to achieve sustainable competitive advantage. However, firms can also decide to cooperate with each other through mobilization of resources to ensure mutual benefit and thus promote healthy competition. A strategic dilemma may occur for competing firms to cooperate with other who traditionally believe in competition, profit orientation, and self-interest. This paper tries to address firm level responses and interactions amongst each other in various consequences by  relying on exploratory method of research. Firms competing in the same industry may opt for four different strategic options named as , competition, cooperation, coexistence and coopetition. Through the literature review, different forms of firm level relationships are explained under these four strategic options. This paper argues that cooperation is beneficial and may complement healthy competition amongst competing firms. JEL Classification Code:  L10, L14
Keywords: Cooperation; Competition; Strategy; Competitive advantage